2022
DOI: 10.3389/fpsyg.2022.863688
|View full text |Cite
|
Sign up to set email alerts
|

Gender Self-Confidence as a Protective Factor for Suicide Risk: Analysis of the Sample of Lithuanian Men

Abstract: BackgroundAlong with other suicide risk factors, masculinity has been analyzed as an important subject for suicidal behavior in men. This study examines masculinity as a gender self-confidence which is the intensity of an individual's belief that he meets his standards for masculinity. We use Hoffman and her colleague's concept, which provides two theoretical constructs as elements of gender self-confidence: gender self-definition and gender self-acceptance. Gender self-definition relates to how salient mascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(42 reference statements)
0
4
0
1
Order By: Relevance
“…Although conformity to masculine norms has generally been associated with worse health outcomes, Gerdes and Levant ( 2018 ) found that a few norms were associated with positive results, particularly health promotion. Similarly, some dimensions of masculinity may be protective of suicide risk (Grigiene et al, 2022 ), including through enactment of the protective father role and viewing help‐seeking as a way to regain self‐control during times of severe depression (Oliffe et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although conformity to masculine norms has generally been associated with worse health outcomes, Gerdes and Levant ( 2018 ) found that a few norms were associated with positive results, particularly health promotion. Similarly, some dimensions of masculinity may be protective of suicide risk (Grigiene et al, 2022 ), including through enactment of the protective father role and viewing help‐seeking as a way to regain self‐control during times of severe depression (Oliffe et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The general population sample consisted of 445 adult men (age between 18–59, M = 26.60, SD = 12.42) from the Lithuanian general population quota (based on age and residential area) sample. The original collected general population sample consisted of 562 men (a detailed description of the sample is published elsewhere [ 19 ]); however, for the purpose of the current study, the oldest age groups of 60+ were dropped to match the overall age interval with that of the regular active duty soldier sample.…”
Section: Methodsmentioning
confidence: 99%
“…The data of the general population sample came from another research study carried out recently by the Suicide Research Centre between June 2020 and April 2021. A detailed description of the general population data collection procedure is published elsewhere [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrimas Švedijoje parodė, kad vyrai, kurie užsiima vyrišku laisvalaikiu (pavyzdžiui, sportu, medžiokle, žvejyba) ar vyriškomis darbinėmis veiklomis (pavyzdžiui, miškininkyste, mechanika), rečiau miršta dėl savižudybės (Månsdotter et al, 2009). Kiti tyrimai taip pat byloja, kad stipresnis vyriškas tapatumas ir pasitikėjimas savo vyriškumu (Grigienė et al, 2022) bei labiau išreikšti vyriški bruožai yra susiję su mažesne savižudybės rizika (Hunt et al, 2006). Vis dėlto tame pačiame Hunt ir kt.…”
Section: įVadasunclassified